Classical swine fever in Victorian domestic pigs: evidence of disease freedom. Issue 11 (1st September 2019) - Hunnam, JC; Moore, KM; Daniel, P; Stevenson, MA; Salmon, SE
Abstract : Objective: Australia is currently regarded as free of classical swine fever (CSF), a highly contagious disease of pigs caused by a pestivirus. This study aimed to provide additional evidence that the Victorian domestic pig population is free of CSF. Design: A structured representative sero‐prevalence survey of Victorian domestic pigs at slaughter. Method: Three‐hundred and ninety‐one pigs from 23 holdings were sampled at the time of slaughter between March 2016 and October 2017. Results: All samples were negative for CSF virus Ab on ELISA. Because of uncertainty in the sensitivity of the CSF Ab ELISA, estimates of the true prevalence of CSF were calculated using Bayesian methods. The median and upper bound of the 95% credible intervals for the true prevalence of CSF was zero when the diagnostic sensitivity of the CSF Ab ELISA was assumed to range from 0.75 to 0.95. Conclusion: These results provide evidence that the population of domestic pigs in Victoria in 2016‐2017 was free of CSF.